Love Scam as a Manifestation of Online Gender-Based Violence: Aligning Legislation to Ensure Victim Protection - Maulidia Mulyani (Istinbath : Jurnal Hukum, 2025)
Love scams, increasingly prevalent in Indonesia, represent a new form of gender-based violence in the digital world. This study aims to trace the history of love scams as a manifestation of online gender-based violence, identify the patterns of manipulation used, and assess the adequacy of legal protection for victims within the framework of applicable regulations. Using a legal-normative approach and qualitative content analysis, this research examines secondary data consisting of legal regulations, court rulings, and actual case studies involving victims. Findings show that love scams not only have financial consequences but also leave deep psychological trauma due to emotional manipulation in fictitious relationships. This pattern of violence is formed through five stages: creating an attractive identity, seduction, requests for money, online sexual harassment, and the revelation of lies. However, the three main legal instruments in Indonesia—the TPKS Law, the ITE Law, and the Penal Code—do not explicitly regulate love scams as digital gender-based violence, leaving legal loopholes that harm victims. This study emphasizes the importance of harmonizing regulations with the principle of responsive law, so that legal protection is more adaptive to technological developments and the complexity of gender-based violence in cyberspace.